Environmental Factors As The Risk Factors Of The Degrees Severity Chronic Obstructive Pulmonary Diseases on Elderly - Novie, Novie Elvinawaty Mauliku; Desintra, Desinta Estri Dianis (JURNAL KESEHATAN KARTIKA, 2021)
Chronic Obstructive Pulmonary Disease (COPD) is a disease characterized by limited air flow that is not entirely reversible. The People with COPD in Indonesia are estimated to reach 4.8 million with a prevalence of 5.6% and rank first with morbidity(35%).COPD can cause damage to the structure of the respiratory tract and result in narrowing of the respiratory tract. This study aims to determine the relationship of environmental factors with the severity of COPD in the elderly at BBKPM Bandung. The study design was used crosssectional. The population of this study was all the elderly who treated at BBKPM Bandung in 2017 as many as 51 people with a total sampling technique. A questionnaires and GPS Distance Meters were used as the research instruments. The results showed that there was a relationship between smoking history (p = 0.038) and house distance to pollutant sources (p = 0.014). Whereas the unrelated variables were occupational history (p = 0.956) and biomass exposure at home(p = 0.189), it can be concluded that there is a correlation between the history of smoking and distance of the house with COPD severity in the elderly.